Functional characterisation of CD8+ T cells mobilised with acute supramaximal high‐intensity interval exercise: implications for immune surveillance - Anna Strömberg; Mirko Mandić; Brennan J Wadsworth; Sebastian Proschinger; Seher Alam; Lisa MJ Eriksson; Laura Barbieri; Eric Rullman; Helene Rundqvist (Clinical & Translational Immunology, 2025)
Abstract Objectives The beneficial influence of exercise on outcomes such as infection control and cancer prevention has been attributed partly to the immune system response during physical exertion. CD8+ T cells play a crucial role in immune surveillance, and in this study, we performed an in‐depth analysis of the impact of supramaximal high‐intensity exercise (HIIT) on CD8+ T‐cell dynamics and function, which are currently lacking in the literature. Methods CD8+ T cells obtained from healthy human subjects before and after 3 × 30 s of HIIT were analysed ex vivo for viability and expansion properties, metabolic function using SeaHorse, IFN‐gamma release using EliSpot, phenotype using RNA‐seq and flow cytometry, and cytotoxic capacity by co‐culture with HEK293T cells. Results Exercise led to a threefold increase in CD8+ T‐cell count, and CD8+ T cells obtained after exercise had a more cytotoxic profile. Post‐exercise CD8+ T cells had a lower glycolytic capacity than pre‐exercise cells, and incubation of pre‐exercise CD8+ T cells with post‐exercise serum replicated this metabolic shift, suggesting a systemic effect of exercise on CD8+ T‐cell metabolism. Importantly, CD8+ T cells maintained their viability and expansion properties despite the metabolic challenges induced by exercise. Functionally, post‐exercise CD8+ T cells showed increased release of IFN‐gamma and an enhanced unspecific cell killing capacity as demonstrated by co‐culture with the immortalised cell line HEK293T. Conclusion The pronounced increase in the total number of circulating CD8+ T‐cells with an increased cytotoxic capacity suggests a potential improvement in immune surveillance after acute HIIT.